POLITIK EKONOMI DAN KEMISKINAN (STUDI KOMPARATIF POLITIK EKONOMI KAPITALIS, SOSIALIS, DAN ISLAM) - Hidayat, Hidayat (WEDANA: Jurnal Kajian Pemerintahan, Politik dan Birokrasi, 2019)
Poverty is a condition when the inability to fulfill basic needs such as clothing, food, shelter, education, health, security. Poverty is a classic problem that is increasing day by day. Even though the news conveyed has decreased in average (aggregate), in fact poverty has always increased. A fundamental solution is needed in overcoming the problem of poverty, because the existing poverty condition is the background for the birth of other social problems, such as crime, violence, and even committing kufr (apostasy). The application of the Capitalist-Liberal Political System and Socialism-Communist has proved to be a failure in solving the problem ofpoverty. Even from the application of this system, it creates structural poverty in the community. A different reality from the application of the Islamic Political Economy system, in which the State guarantees the fulfillment of the basic needs of each person as a whole, as well as the possibility of himself fulfilling his secondary and tertiary needs, according to the level of ability as an individual who lives in a society that has a lifestyle ( life style). Guarantee the fulfillment of primary needs (clothing, food, shelter, education, health, and security) is carried out through various mechanisms, either directly or indirectly. So, by implementing it will minimize the poverty rate, and also allow the poverty rate to be zero percent. It has been historically proventhat at the time of the Caliph Umar Ibn Abdul Aziz radhiallahu 'anhu, state officials had difficulty finding the poor / poor in distributing zakah assets.